2014
DOI: 10.1007/s00330-014-3243-5
|View full text |Cite
|
Sign up to set email alerts
|

Optimising the preoperative planning of deep inferior epigastric perforator flaps for breast reconstruction

Abstract: DIEP flap is one of the best techniques for breast reconstruction. Preoperative planning is essential in DIEP flaps. CTA is the best option for the preoperative planning of DIEP flaps. "Navarra criteria" allow radiologists to choose the best perforator to form flaps. Modified "Navarra criteria" improves radiological and surgical concordance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…There are some discrepancies in literature concerning the agreement rate of CTA versus intraoperative perforator selection. Some authors report as high as 95.2% (Casares Santiago et al, 2014), 74% (Haddock et al, 2020), or 67.3% (Boer et al, 2017) while others revealed nearly half of DIEP flaps had been harvested with changes from the surgical planning due to insufficient information from preoperative CTA (Keys et al, 2013). Haddock et al (2020) found in their study that when used for preoperative planning, CTA reduced operative time by over 1 h. However their study only includes bilateral DIEP patients, which is relevant since there is no concern for fat necrosis of zone III.…”
Section: Discussionmentioning
confidence: 99%
“…There are some discrepancies in literature concerning the agreement rate of CTA versus intraoperative perforator selection. Some authors report as high as 95.2% (Casares Santiago et al, 2014), 74% (Haddock et al, 2020), or 67.3% (Boer et al, 2017) while others revealed nearly half of DIEP flaps had been harvested with changes from the surgical planning due to insufficient information from preoperative CTA (Keys et al, 2013). Haddock et al (2020) found in their study that when used for preoperative planning, CTA reduced operative time by over 1 h. However their study only includes bilateral DIEP patients, which is relevant since there is no concern for fat necrosis of zone III.…”
Section: Discussionmentioning
confidence: 99%
“…The use of high-resolution vascular mapping preoperative tests on microsurgical flaps has been shown to decrease intraoperative complications in flap dissection [ 21 ], decrease overall surgical time and flap harvesting time [ 22 ], facilitate dissection and avoid serious vascular complications [ 23 ] in patients with vascular abnormalities that could not be diagnosed without such vascular tests or only with physical examination [ 22 , 23 , 24 ]. There is published evidence on the improvement of results when performing preoperative vascular mapping studies with MRA and CTA in several microsurgical flaps: fibula flap [ 24 , 25 , 26 , 27 ], deep inferior epigastric perforator flap [ 21 , 22 , 23 , 28 , 29 , 30 , 31 ] and other perforator flaps. The evidence for the use of preoperative vascular mapping tests in RFFF is scarce, with contradictory results.…”
Section: Discussionmentioning
confidence: 99%
“…The deep inferior epigastric perforator (DIEP) flap is the most common flap used in breast reconstruction. Raising a DIEP flap requires meticulous dissection of the DIEP vessels; however, there is significant heterogeneity in their branching pattern and location [ 132 ]. CTA is the current ‘gold standard’ for pre-operative vascular mapping, reducing operative time and postoperative complications [ 133 135 ].…”
Section: Notes On Specific Protocolsmentioning
confidence: 99%